Kualitas Pelayanan, Customer Relationship Marketing, dan Kepuasan Pelanggan sebagai Determinan Loyalitas Pelanggan - Ulum, Panji; Widya Pratiwi; Delvita Juniarsih; Relya Contesa (Indo Publishing, 2025)
This study aims to analyze the influence of service quality , Customer Relationship Marketing (CRM) , and customer satisfaction on customer loyalty at the official Honda AHASS workshop “Sahabat Motor” in Margo Tabir. The research method used is a quantitative approach with multiple linear regression analysis. The sample consisted of 96 respondents selected using Simple Random Sampling technique. Regression test results show that service quality, CRM, and customer satisfaction have a positive and significant effect on customer loyalty, both partially and simultaneously. The coefficient of determination (R²) of 0.434 indicates that the three independent variables explain 43.4% of the variation in customer loyalty, while the remaining percentage is influenced by other factors outside the study. Based on these findings, the workshop is advised to improve customer interaction quality, strengthen CRM programs, and conduct periodic evaluations of customer satisfaction levels to enhance retention and customer loyalty.